Description of the female of Lyssomanes miniaceus, with a new distribution record for L. belgranoi (Araneae: Salticidae) - Gonzalo D. Rubio; William Galvis; María F. Nadal (Caldasia)
Numerous new spider species are waiting to be described, and in many cases knowledge is incomplete because species are known from a single sex. In this contribution the female of the jumping spider Lyssomanes miniaceus is described and its morphology is illustrated. Females are distinguished by having spherical, slightly oval spermathecae, the copulatory openings towards the back, and sparse white hairs ventrally on femora I and II; the last character could be a unique trait shared by both sexes. Additionally, a new southernmost record plus new illustration of the little-known species L. belgranoi are given.